1999
DOI: 10.1002/j.1556-6978.1999.tb01220.x
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors as Supervisors: An Integrated Approach for Supervising School Counseling Interns

Abstract: This article proposes an approach for supervising school counseling interns. The approach integrates supervisor roles, intern skills, and stages of the supervision process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Samples of these recommendations include peer supervision (Agnew, Vaught, Getz, & Fortune, 2000;Borders, 1991;Crutchfield & Borders, 1997), peer consultation (Benshoff & Paisley, 1996), group supervision Gainor & Constantine, 2002), and clinical supervision (Henderson & Lampe, 1992;Sutton & Page, 1994). Several authors have focused their work specifically on theories, models, and modalities of supervision that attempt to address the practice of supervision for professional school counselors (Borders, 1989;Getz 1999;Nelson & Johnson, 1999;Page, Pietrzak, & Sutton, 2001;Peace, 1995;Protivnak, 2003).…”
mentioning
confidence: 99%
“…Samples of these recommendations include peer supervision (Agnew, Vaught, Getz, & Fortune, 2000;Borders, 1991;Crutchfield & Borders, 1997), peer consultation (Benshoff & Paisley, 1996), group supervision Gainor & Constantine, 2002), and clinical supervision (Henderson & Lampe, 1992;Sutton & Page, 1994). Several authors have focused their work specifically on theories, models, and modalities of supervision that attempt to address the practice of supervision for professional school counselors (Borders, 1989;Getz 1999;Nelson & Johnson, 1999;Page, Pietrzak, & Sutton, 2001;Peace, 1995;Protivnak, 2003).…”
mentioning
confidence: 99%
“…The recommendation to train school counselors for the specific on-site mentoring role seems to be an imperative and is consistent with prior recommendations (e.g., Jackson et al, 2002;Kahn, 1999;Nelson & Johnson, 1999;Peace & Sprinthall, 1998;W. B. Roberts & Morotti, 2001;Studer, 2005;Sumerel & Borders, 1996).…”
Section: Conclusion Limitations Recommendations and Future Researchmentioning
confidence: 73%
“…Overall, the results of the analysis regarding the ideal mentor revealed that when given the opportunity to express their perceptions openly and at length, mentors and interns alike refer first and foremost to professional and personal traits, to the mentoring relationship, and to the mentor's attitudes toward the role. These seem to be essential preconditions and dispositions perceived as necessary to the role and are also mentioned in the professional literature (e.g., CACREP, 2001; Israeli Ministry of Education, Division of Psychological and Counseling Services, 2000; Nelson & Johnson, 1999;SINACES, 1993;Studer, 2005;Tentoni, 1995;White & Queener, 2003). The priority attributed to professional traits by both groups indicates that the respondents consider that the profession of counseling should be learned from highly effective, experienced, and well-established professional counselors.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The Make It Happen program was initially designed and implemented in a participatory way, in which students, university faculty, school staff, mentor counselors, and counselors in training partnered and worked together to design the group curriculum based on the students' needs and input (Nelson & Johnson, 1999;Smith, Davis, & Bhowmik, 2010). The initial curriculum was tested and improved through a pilot study at nine schools.…”
Section: Description Of the Make It Happen Programmentioning
confidence: 99%